Boosting Swiss Chard Germination with Atmospheric Pressure Plasma Jet - Thakur, Bablu K.; Shah, Arun K.; Sah, Ram L.; Silpakar, Reeta; Shrestha, Rajendra; Mishra, Lekha N. (Journal of Nepal Physical Society, 2025)
This study was carried out to reveal the effect of non thermal atmospheric pressure plasma jet on germination of Swiss chard seed. The Atmospheric Pressure Plasma Jet has been characterized by electrical and optical methods. The electron density and electron temperature have been determined by power balance, and Boltzmann plot method respectively. A cold APPJ with argon gas source was employed in this study. APPJ has been generated using high voltage power supply (0 - 20 KV) and high frequency (27 MHz). The electron density was found to be 1.68 × 1020 m−3 and average electron temperature was estimated to be 0.73 eV. The effects of different duration of plasma jet on germination of the Swiss chard seed was studied. The Swiss chard seed was treated by plasma for different duration of time.